Essence of Innovative Pedagogical Activity - Yurii Zavalevskyi (Pedagogical Discourse, 2014)
The question of development of education in Ukraine taking into account eurointegration that stipulated the necessity of development of innovative processes for educational branch has been considered in the article. The necessity of changes in the activity of a teacher which will result in high-quality changes in educational process of general educational establishment and approaching of its results to the standards of European educational space has been grounded. The analysis of problems of modern education has been done. The components of professional readiness of a teacher have been determined and the accent on the advantages of innovative pedagogical activity has been made.